2007
DOI: 10.1111/j.1600-0684.2007.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Invariant natural killer T cells from rhesus macaque spleen and peripheral blood are phenotypically and functionally distinct populations

Abstract: Spleen iNKT cells in rhesus macaques are Th2 biased and display phenotypically and functionally distinct profiles from their PB counterpart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 63 publications
3
18
0
Order By: Relevance
“…2A). Consistent with some previous reports of studies using rhesus macaques (14,20), very few NKT cells in the animals tested carried the CD4 Ϫ CD8 Ϫ phenotype that is common for mice and humans.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…2A). Consistent with some previous reports of studies using rhesus macaques (14,20), very few NKT cells in the animals tested carried the CD4 Ϫ CD8 Ϫ phenotype that is common for mice and humans.…”
Section: Resultssupporting
confidence: 79%
“…It was possible that spleen-derived NKT cells examined in the latter study (27) are different from blood-derived NKT cells. A recent study (14) directly compared rhesus macaque blood and spleen-derived NKT cells and found that most spleen NKT cells were CD4 ϩ CD8 ϩ , compared to blood, where most NKT cells were CD4 Ϫ CD8 ϩ , although even in blood, 20% were reported to be CD4 ϩ CD8 ϩ . Our results are not exactly consistent with any of the previous studies, but this may be due to the fact that we have used pigtailed macaques versus the use of rhesus macaques in all previous studies.…”
Section: Vol 83 2009 Nkt Cells In Siv-positive Macaques 1621mentioning
confidence: 99%
See 1 more Smart Citation
“…The specificity of 6B11 was defined by binding to the cyclic peptide used as antigen, reactivity with Jurkat cells transfected to express the iNKT TCR, reactivity to T cells derived from a mouse that expressed a human invariant AV24AJ18 TCR a-chain, and selection for and activation of iNKT clones and lines in vitro. Although raised in CD1d KO mice, 6B11 did not react with murine iNKT (or other murine) cells (data not shown), but does react with iNKT cells of rhesus macaques, non-human primates [37]. To our knowledge, this antibody is the only anti-CDR3 idiotype-specific mAb available for a TCR of known specificity.…”
mentioning
confidence: 88%
“…Hybridomas secreting antibodies reactive with invariant peptide were screened for reactivity against the DN2.D6 and other iNKT clones and for reactivity against control unrelated T cell clones by indirect immuno-staining with anti-IgG FITC as described [2,32,37]. Briefly, T cells were suspended in FACS buffer (PBS, 1% FBS and 0.1% NaN 3 ) in a 96-well plate.…”
Section: Screening For Invariant Tcr-reactive Antibodiesmentioning
confidence: 99%